Bioinspired nanostructured hydroxyapatite/collagen three-dimensional porous scaffolds for bone tissue engineering. Issue 46 (23rd May 2015) - Guan, Junjie; Yang, Jun; Dai, Junqi; Qin, Yunhao; Wang, Yang; Guo, Yaping; Ke, Qinfei; Zhang, Changqing
<x xml:space="preserve">Abstract</x> A needle punching and bioinspired mineralization strategy has been developed to fabricate a collagen/hydroxyapatite porous scaffold for bone tissue engineering.